Sodium trimetaphosphate enhances the effect of 250 p.p.m. fluoride toothpaste against enamel demineralization in vitro - Missel, Emilene M. C. [UNESP]; Cunha, Robson F. [UNESP]; Vieira, Ana E. M. [UNESP]; Cruz, Nathália V. S. [UNESP]; Castilho, Flavia C. N. [UNESP]; Delbem, Alberto C. B. [UNESP] (Wiley, 2016)
This in vitro study investigated the effect of sodium trimetaphosphate (TMP), added to toothpaste containing 250 p.p.m. fluoride, on enamel demineralization. Bovine enamel blocks (n = 96) were subjected to five pH cycles over a 7-d period and treatment with suspensions of toothpastes containing 0, 250, 500, and 1,100 p.p.m. fluoride (as sodium fluoride), as well as with 250 p.p.m. fluoride containing TMP at 0.25, 0.5, 1.0, and 3.0%. Treatment with toothpaste suspensions was performed under agitation twice a day, for 1 min. Surface and cross-sectional hardness, and fluoride firmly bound to enamel, were quantified. Data were subjected to one-way anova, followed by Tukey's test. Low-fluoride toothpastes containing TMP at 0.25–1.0% resulted in enamel mineral loss similar to that seen for the toothpaste containing 1,100 p.p.m. fluoride. Also, the addition of TMP to the toothpaste containing 250 p.p.m. fluoride promoted enamel fluoride concentrations similar to those obtained for the 500 p.p.m. fluoride group. The toothpaste containing 250 p.p.m. fluoride and 0.25% TMP led to the lowest mineral loss among all groups. It was concluded that the addition of as little as 0.25% TMP to a toothpaste containing 250 p.p.m. fluoride can reduce enamel demineralization to levels similar to those seen for a conventional toothpaste containing 1,100 p.p.m. fluoride, in vitro.
Keywords: fluoride; phosphates; tooth demineralization; toothpastes